ANALYSIS OF FACTORS AFFECTING THE INTEREST IN INFAQ AMONG BSI CUSTOMERS IN BANJARMASIN CITY - Muhammad Rizky Firdaus; Mahyuni Mahyuni (INJOSEDU: International Journal of Social and Education, 2025)
The purpose of this study is to analyse the influence of factors such as benefits, altruism, and nominal flexibility on the interest in infaq among customers of Bank Syariah Indonesia (BSI) in Banjarmasin City. Infaq is a form of worship in Islam that can be channelled through Islamic financial institutions such as BSI. This study uses a quantitative approach with a survey method and data collection through questionnaires given to 100 respondents. The data analysis technique used is multiple linear regression with the help of SPSS 22 software. The results of the study indicate that the three independent variables—benefits of infaq, altruism, and nominal flexibility—have a significant influence on interest in infaq. Altruism has the most dominant influence, followed by the benefits of infaq and flexibility. Together, these three factors contribute 64.6% to customers' interest in infaq. These findings have practical implications for BSI to enhance its education and infaq programmes by emphasising spiritual benefits, moral values, and transaction ease tailored to individual capabilities.